2009
DOI: 10.1590/s1808-86942009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer: population sample of the state of Alagoas at a reference hospital

Abstract: The incidence and mortality of oral cancer in Brazil remains high; the disease manifests varying features throughout the country. Aim: To analyze the epidemiology of oral cancer, including the prevalence, type and site of lesions, the distribution in the state of Alagoas, staging, treatment, and social and demographic aspects. Material and Methods: A descriptive retrospective study was carried out. Data were gathered from records of a hospital in Alagoas from January 2000 to December 2006. Results: Of 396 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
(14 reference statements)
1
3
0
9
Order By: Relevance
“…Não foram identificadas, no presente estudo, associações entre as variáveis epidemiológicas/clínicas e o atraso do paciente, de forma semelhante ao encontrado por Santos et al 5 , provavelmente porque a população do estudo, em sua maioria, é muito desfavorecida. Em pesquisa realizada em Juiz de Fora, em Minas Gerais, os pacientes de zona rural, solteiros e do sexo masculino foram os que exibiram maior atraso no diagnóstico 3 . O atraso profissional no presente estudo foi de 20 dias, semelhante a outros trabalhos nacionais 5,19 e quase o dobro do tempo de trabalho realizado nos Estados Unidos (10,1 dias) 19 .…”
Section: ▄ Discussãounclassified
See 1 more Smart Citation
“…Não foram identificadas, no presente estudo, associações entre as variáveis epidemiológicas/clínicas e o atraso do paciente, de forma semelhante ao encontrado por Santos et al 5 , provavelmente porque a população do estudo, em sua maioria, é muito desfavorecida. Em pesquisa realizada em Juiz de Fora, em Minas Gerais, os pacientes de zona rural, solteiros e do sexo masculino foram os que exibiram maior atraso no diagnóstico 3 . O atraso profissional no presente estudo foi de 20 dias, semelhante a outros trabalhos nacionais 5,19 e quase o dobro do tempo de trabalho realizado nos Estados Unidos (10,1 dias) 19 .…”
Section: ▄ Discussãounclassified
“…O carcinoma espinocelular (CEC) representa mais de 90% de todos os casos de câncer de boca 2 . Estudos realizados por Santos et al 3,4 e Santos et al 5 revelaram que a maioria dos pacientes com câncer de boca em Alagoas pertence à faixa etária entre 50 a 60 anos de idade, é do sexo masculino, possui baixa renda, reside no interior do Estado e é analfabeta ou analfabeta funcional. Para esses autores, esses pacientes são mais vulneráveis e possuem uma maior dificuldade de acesso aos serviços de saúde, o que pode refletir diretamente nas taxas de mortalidade e morbidade do câncer bucal.…”
Section: ▄ Introduçãounclassified
“…1 The literature is vast regarding estimated occurrences of oral lesions such as oral cancer, [2][3][4] as well as odontogenic 5,6 and salivary gland tumors. [7][8][9][10] Contrarily, only few studies have documented the frequency of histologically confirmed lesions in adults, [11][12][13][14] and data are particularly scarce in Brazil.…”
mentioning
confidence: 99%
“…5,10,18 The majority of patients were diagnosed at advanced stage of cancer (stage III and IV). According to Ruback et al 19 and Santos et al 20 a high proportion of cancer patients is only diagnosed at advanced stage, and demonstrates the difficulty in obtaining an early diagnosis. This is probably due to lack of patients' knowledge about head and neck cancer, as the symptoms are not incapacitating in early stages, and the hospital fee is either too expensive or they choose alternative medicine instead of going to see a doctor.…”
mentioning
confidence: 99%